Mercapto-Benzamide Inhibitors effects on HIV NCp7 Protein: a parameter-free DFT based structural study. Issue 1 (1st November 2022) - Cappellini, G; Cardia, R; Valentini, M; Pieroni, E
Abstract : The action of the Mercapto-Benzamide (MB) class of molecules on the HIV Nucleocapsid protein (HIV NCp7), a zinc finger protein, is an issue of relatively recent research interest, relevant to develop a new class of effective and well tolerated HIV antivirals, able to overcome virus escape strategies. MB molecules are easily and cheaply synthesized, and show the ability to unfold the HIV Zinc-finger region, thus avoiding effective viral replication. This effect is not still fully understood, and moreover is highly influenced by the precise composition of MB aromatic ring and chain. Our approach to this biological problem is to adopt a quantum parameter-free (ab-initio: AI) geometrical scheme based on density functional theory (DFT) for the treatment of the electronic degrees of freedom to study with atomistic resolution the action mechanism of MB molecules on NCp7. In particular with respect to the role played by each MB functional group.We report and discuss the outcomes of the here proposed DFT simulations with respect to the different final configurational structures obtained.